Penyuluhan Pertolongan Pertama pada Kecelakaan Kerja Tertusuk Benda Tajam pada Kuli Bangunan - Islamy, Aesthetica; Farida, Farida; Yitno, Yitno; Masruroh, Eny; Audilla, Amita; Yuliastuti, Wiwid; Lasman, Lasman; Suharyoto, Suharyoto; Suciati, Suciati; Nurhidayati, Nurhidayati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Injury is a condition in which the anatomical structure of body tissues is disturbed. Injuries can be superficial, such as damage to the epithelium of the skin, or deep, involving subcutaneous tissue, fat, and muscle, as well as bone and related structures, such as tendons, nerves, and blood vessels resulting from trauma and physical force. The purpose of this activity is to provide knowledge to construction workers as an effort to change the target attitude about First Aid in Construction Workers Affected by Vulnus Puncture. Method: This activity is divided into 4 stages, namely the stage of problem analysis, planning, implementation and evaluation. Evaluation is obtained with 2 types, namely knowing immediate impect and intermediate impact. The target group in this activity is 34 construction workers domiciled in Jabon Village. Results: most of the targets before counseling, most had negative attitudes (n = 23 (68%)), then after counseling, most respondents had positive attitudes (n = 27 (79%)). The results of immediate impact measurements showed a positive response from the target and the results of statistical tests (Wilcoxon) to analyze intermediate impact obtained ρ value results of 0.000 with a α of 0.05. This value indicates a significant conclusion of results. Conclusion: There are benefits in extension activities as evidenced by responses and statistical test results of attitude categories before and after counseling. Counseling is one way of providing information that can involve affective, conative and psychomotor elements, so that respondents absorb knowledge optimally.